The Preception of Trans Batam Pasenger Due to The Increase in Fuel Prices - Rahmat Hermawan; Andri Irfan Rifai; Usmanul Hayadi Umar (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The development of world transportation modes is improving. facilities and infrastructure to be able to facilitate mobilization can now be accessed anywhere. Transportation also plays a role in the development of an area because the function of transportation can also be said to be one of the supports for the economy and regional development in an area. This research wants to find out the interest of Batam residents in Trans Batam due to the increase in fuel as an alternative to the use of daily transportation modes Design/methodology/approach: Data obtained from the results of the Trans Batam user questionnaire survey using the method of expressing preferences and using variables in the form of tariffs, timeliness, service quality, information availability, safety, comfort, cleanliness, availability of facilities, availability of routes, and interest in using Trans Batam. The survey results were then carried out a comparative analysis using a spider web model from questionnaire data that had been shared with 100 respondents. Findings: The survey results were then conducted in a comparative analysis using a spider web model from questionnaire data that had been shared with 100 respondents. The findings are that there are improvements in performance in tariffs, service quality, and availability of facilities. Meanwhile, on timeliness, information availability, and safety, there are no significant performance changes. However, there is a decrease in performance on the comfort, cleanliness, and availability of routes. The conclusion obtained from the results of this study is that there is an increase in interest of Batam residents in Trans Batam due to the increase in fuel prices. Research limitations/implications: Most of the data collection in the implementation of this research was carried out by distributing questionnaire links anonymously, so it is possible that there were respondents who filled them out at random so that the quality of the data was lacking. Practical implications: Tariffs are the main factor for potential consumers in choosing public transportation modes. There are also two other factors contributing to the increasing interest of Batam residents in Trans Batam, that is the quality of service and the availability of facilities. Originality/value: This paper is an original work. Paper type: Research paper